Performing Gender, Doing Politics: Social Media and Women Election Workers in Kerala and Tamil Nadu - Charles, Drupa Dinnie; Meena, Azhagu; Lalvani, Simiran; Akbar, Syeda Zainab; Siddarth, Divya; Pal, Joyojeet (ICTD 2020, 2020)
Women political workers adopt a range of tactics to navigate the hyper-masculine space of electoral politics in South India, both offline and, increasingly, online. Using interviews and observations over three months of election campaigning, we examine women's outreach work in online and offline adversarial spaces through the lens of Michel de Certeau's, The Practice of Everyday Life, which examines the "tactics" through which people negotiate change and everyday challenges in daily situations. We find that the everyday logistics of election work have changed significantly, and that these bring up two important ways in which "tactics" framework is helpful - first, in the changing ways in which representations need to be managed, as political work requires an interactive digital public face, and second, in ways that which online interactions need to be managed as new and increasingly demanding forms of communication are necessitated for effective voter outreach.